Communication models in a foreign language in relation to cognitive style category width and power distance - Munkova, Dasa; Stranovska, Eva; Munk, Michal (Frontiers in Psychology, 2024)
Understanding how category width of cognitive style and power distance impact language use in cultures is crucial for improving cross-cultural communication. We attempt to reveal how English foreign language students, affected by high-context culture, communicate in an English as a foreign language. What models of foreign communicative competence do they create? We applied association rule analysis to find out how the category width of cognitive style affects the foreign communication competence in relation to culture and language. The requester tends to be more formal and transfers conventional norms of culture of mother tongue into English, which mainly affects the use of alerters and external modifications of head act of request. A broad categorizer, regardless of social distance, prefers to formulate the request in a conditional over the present tense form, contrary to narrow categorizers who, in a situation of social proximity, prefer the request form in present tense. A similar finding was shown in the case of external modifications of the head act, where we observed the inversion between broad and narrow categorizers, mainly in the use of minimizers and mitigating devices.